A preliminary seismic travel time tomography beneath Ecuador from data of the national network. (November 2021) - Araujo, Sebastián; Valette, Bernard; Potin, Bertrand; Ruiz, Mario
Abstract: The subduction of the Nazca plate has specific features that impact the geophysical structure beneath Ecuador. In addition to the convexity of the trench between Peru and Ecuador, the Carnegie ridge and the Grijalva scarp are associated with strong heterogeneities in the plate that interfere with the subduction process. We have taken advantage of the large amount of manually picked P and S wave arrival times accumulated over time thanks to the national RENSIG network to perform an inversion for both event locations and seismic velocities over Ecuador within lat. 1.5 ∘ N and 5 ∘ S and long. 77 ∘ W and 82 ∘ W. After data filtering, the model presented in this article results from the inversion of 335, 498 P and 111, 457 S arrival times, corresponding to 25, 410 events between 1988 and 2016. The intermediate depth seismicity outlines a continuous Wadati-Benioff zone in southern Ecuador that clearly defines the topography of the Farallon plate and its plunge towards the north-east at the Puyo nest, whereas in the northern part of the slab its pattern is more heterogeneous and is dominated by three nests at depths ranging between 75 km and 110 km, the Guayaquil, La Maná and Maldonado nests. The velocity model reveals a discontinuity of the Nazca plate along an axis oriented N110 ∘ E, starting in the seismogenic zone at the southern limit of the occurrence of large earthquakes. This tear is associated with an overlap of the southern Farallon part of the slab by its younger northern part. We propose that it is the result of plate buckling due to lateral compression at depth caused by the sharp bend of the trench line between Peru and Ecuador. Highlights: First seismic tomography survey for the Ecuadorian region using the data of Ecuadorian Seismic Network RENSIG. An anomaly in the Nazca slab structure produced by the buckling or the tearing of the tectonic plate. A description of the structure of the Crust below the Forearc and the Andean regions. Position of the primary magmatic volcano chamber below the cordilleras. Detailed relocation of the seismicity at intermediate depth to precise the seismic nest produced by the subduction dynamics.